Mistrust in marriage-Reasons why men do not accept couple HIV testing during antenatal care- a qualitative study in eastern Uganda - Popenoe Rebecca; Namusoko Sarah; Nsabagasani Xavier; Thorson Anna; Larsson Elin C; Ekström Anna (BMC, 2010)
Abstract Background A policy for couple HIV counseling and testing was introduced in 2006 in Uganda, urging pregnant women and their spouses to be HIV tested together during antenatal care (ANC). The policy aims to identify HIV-infected pregnant women to prevent mother-to-child transmission of HIV through prophylactic antiretroviral treatment, to provide counseling, and to link HIV-infected persons to care. However, the uptake of couple testing remains low. This study explores men's views on, and experiences of couple HIV testing during ANC. Methods The study was conducted at two time points, in 2008 and 2009, in the rural Iganga and Mayuge districts of eastern Uganda. We carried out nine focus group discussions, about 10 participants in each, and in-depth interviews with 13 men, all of whom were fathers. Data were collected in the local language, Lusoga, audio-recorded and thereafter translated and transcribed into English and analyzed using content analysis. Results Men were fully aware of the availability of couple HIV testing, but cited several barriers to their use of these services. The men perceived their marriages as unstable and distrustful, making the idea of couple testing unappealing because of the conflicts it could give rise to. Further, they did not understand why they should be tested if they did not have symptoms. Finally, the perceived stigmatizing nature of HIV care and rude attitudes among health workers at the health facilities led them to view the health facilities providing ANC as unwelcoming. The men in our study had several suggestions for how to improve the current policy: peer sensitization of men, make health facilities less stigmatizing and more male-friendly, train health workers to meet men's needs, and hold discussions between health workers and community members. Conclusions In summary, pursuing couple HIV testing as a main avenue for making men more willing to test and support PMTCT for their wives, does not seem to work in its current form in this region. HIV services must be better adapted to local gender systems taking into account that incentives, health-seeking behavior and health system barriers differ between men and women.